Diferentes manejos de irrigação de adubação no progresso da ferrugem do cafeeiro - Barbosa Junior, Mauro Peraro (2015)
Rust is an important disease for coffee. Its occurrence affects nutritional balance and water supply to plants. In certain cases, irrigation can impart greater resistance to the host. However, a provided microclimate can increase the progress rate of the disease. Poor or unbalanced mineral nutrition may predispose plants to fungus infection. Thus, the aim of this study was to evaluate the incidence of rust in coffee plantations with different irrigation and fertilization managements. The study was conducted with adult coffee of cultivar MGS Travessia, in an experimental area of the Department of Agriculture of the Universidade Federal de Lavras, in Minas Gerais, Brazil. Disease ratings were elaborated from March of 2012 to November of 2014. The experimental design was a completely randomized block design, with twelve treatments (3 fertilization managements) x (4 drip irrigated managements) and three replicates, in a total of 36 installments. The results for the average rate of disease incidence was graphically plotted in a disease progress curve for rust incidence (AACPDIF). We observed higher AACPDIF values (P<0.05) in no irrigation (NI) and treatment with suspended irrigation for 70 days (I70) throughout the study period. Plants that have suffered greater water stress were more susceptible to infection.